Introducción a la gestión de proyectos (Assemble You, 2022)
Welcome to Audio Learning by Assemble You. There are very few industries that cannot benefit, in some way, from project management. Whether building a skyscraper, developing new software, installing a plumbing system, designing a housing project, hosting a business convention, or even planning a birthday party, project management is essential for success. The Investopedia team offers us this perfect definition of the term: Project management involves planning and organizing a company's resources to drive a specific task, event, or duty toward completion. It can involve an individual project or an ongoing activity, and managed resources include people, finances, technology, and intellectual property. No matter what the project is, most of the resources listed in that definition are involved in some way, and need to be organized to ensure the project runs smoothly. Learning Objectives Learn about the ways project management can help in almost any industry Learn what project management really entails Learn about some of the most popular project management methodologies.